Application of Nanotechnology in Civil Infrastructure - Krishnaveni, P (International Journal of Computer Sciences and Engineering, 2025)
In this paper, use of engineering in building materials on behalf of a spread of applied science mechanism is mentioned. Strength, sturdiness and different properties of materials are significantly affected underneath a scale of nano meter(10-9m).This paper in addition tells however the employment of nano technology makes concrete more stronger, sturdy and additional simply placed. differing kinds of nano materials used are mentioned with its wide applications. The properties like self-sensing, self- treatment, self-structural health watching are studied. Following this the analysis were applied in versatile structural composites together with its improved properties, low repairs coatings, higher properties of building material materials, reduction of the thermal transfer rate of fireside retardation and insulation, varied nanosensors, sensible materials, intellectual construction technology.